2012
DOI: 10.3126/jnps.v32i2.5673
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Ear Diseases among Paediatric ENT Patient: An Experience from Tertiary Care Centre, Pokhara, Nepal

Abstract: Introduction: Ear diseases are common in children mainly due to altered anatomy of Eustachian tube which is straighter in children as compared to that in adults. However, the cause of hearing loss in children is more varied, including the etiologies. This study was done to find out the pattern of ear diseases in paediatric age group attending ear, nose and throat OPD in a tertiary care centre in Pokhara, Nepal. Materials and Methods: This is a prospective study done in paediatric patients attending ENT OPD ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The study performed by Mishra, et al [11] also found the higher incidence in male as compared to female. This finding is in accordance with other studies [12,13]. The higher prevalence of disease in male has been attributed to their exposure to the outdoor activities and early medical advice seeked as compared to females.…”
Section: Discussionsupporting
confidence: 93%
“…The study performed by Mishra, et al [11] also found the higher incidence in male as compared to female. This finding is in accordance with other studies [12,13]. The higher prevalence of disease in male has been attributed to their exposure to the outdoor activities and early medical advice seeked as compared to females.…”
Section: Discussionsupporting
confidence: 93%
“…Ear disease was a common occurrence in developing countries and mostly affected children (Sigdel and Nepali, 2012;Verina, 2015). A study by Fasunla et al showed that patients with ear disease were 3136 people (62.7%), nose disease was 1153 people (23%), and throat disease was 479 people (9,6%) (Fasunla et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The health of children, including the ear, nose, and throat area is vital for their development and affects the ability to get and understand knowledge. Diseases of ear, nose, and throat (ENT) are common in the populations of the world (Sigdel and Nepali, 2012;Verina, 2015). The understanding of the diseases is important due to their morbidities, which causes dysfunction of physiological functions of the head and neck region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 There was a marginal gender differences in contrast to other studies. 11 The variation could be related to awareness, availability and accessibility.…”
Section: Discussionmentioning
confidence: 99%